Synthesis of Unsymmetrical Aza[7]helicenes by One-Pot Wittig–Heck and Photodehydrogenation Sequence - Rajan, Blessy; Bedekar, Ashutosh V. (Synlett, 2017)
An efficient protocol for the synthesis of unsymmetrical aza[7]helicenes has been developed. The bis-styryl-type substrates for regiospecific photodehydrogenative oxidative double cyclization to give helicenes were prepared by a one-pot Wittig–Heck sequence as well as a stepwise procedure. The derivatives were characterized by single-crystal X-ray diffraction analysis and fluorescence spectroscopy.
Keywords: helical compounds; aza[7]helicenes; one-pot synthesis; Wittig reaction; Heck reaction; photocyclodehydrogenation.